THE ACCESS TO GOVERNMENT FINANCIAL SUPPORT THROUGH LEGAL CHANNELS OF SMALL AND MEDIUM ENTERPRISES IN FOUR ASIA PACIFIC COUNTRIES - Muhamad Marwan (Jurnal Hukum dan Peradilan, 2020)
The aim of this study is to determine the impact of networking on SME’s ability to access government financial support through legal channels in Asia Pacific. This study is quantitative in nature in which the data has been gathered from 281 employees and managers working in SMEs through survey questionnaire. The SEM technique was utilised for the purpose of analysing and testing the mediation effect. The study found that there is a partial mediation of government financial support through legal channels among the relationship between networking with officers and access to finance. This study is restricted to the SMEs operating in the region of Asia Pacific.